2016
DOI: 10.1186/s40508-016-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Castor oil as a potential renewable resource for the production of functional materials

Abstract: Castor oil is increasingly becoming an important bio-based raw material for industrial applications. The oil is nonedible and can be extracted from castor seeds from the castor plant belonging to the family Euphorbiaceae. The oil is a mixture of saturated and unsaturated fatty acid esters linked to a glycerol. The presence of hydroxyl group, a double bond, carboxylic group and a long chain hydrocarbon in ricinoleic acid (a major component of the oil), offer several possibilities of transforming it into variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 55 publications
4
124
0
9
Order By: Relevance
“…It is considered a very important bioresource material for a wide variety of applications [19]. The triglycerides of CO consist of fatty acids (FAs), of which approximately 90% is ricinoleic acid (RA), a hydroxylated monounsaturated 18-carbon carboxylic acid (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a very important bioresource material for a wide variety of applications [19]. The triglycerides of CO consist of fatty acids (FAs), of which approximately 90% is ricinoleic acid (RA), a hydroxylated monounsaturated 18-carbon carboxylic acid (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…After that, the reactions were further evaluated at 100 °C by lowering the catalyst and co-catalyst ratio from 1/0.8 to 0.1/0.1 to get their optimum concentration (Table 1, entry 8-12). It was found that lowering the catalyst and co-catalyst ratio results in a gradual decrease of copolymers average molecular weights from 4950 g/mol to 3100 g/mol (Table 1, entry [8][9][10][11][12]. No improvement in molecular weight was observed even when reaction time was increased from 30 to 50 min (Table 1, entry 10 and 11).…”
Section: Resultsmentioning
confidence: 91%
“…Recently, there have been various approaches and attempts described for the conversion of fatty acids from natural oils [10][11][12][13]. Fatty acid triglycerides from natural oils contain functional moieties, which are limited to certain types of reactions, and need chemical modification to improve their reactivity for the production of higher value products.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that with increasing castor oil content into PUF composition rigidity increased. However, PUF derived from unmodified CO has a relatively low modulus, low thermal stability, and low flame‐retardant properties high curing time due to a secondary hydroxyl group and needs further modification . Recently, Hejna et al .…”
Section: Plant Oil Based Polyurethane Foammentioning
confidence: 99%